Cross-Cultural Differences in Temperament: Comparing Paternal ratings of US and Dutch infants. - Desmarais, Eric (Eur J Dev Psychol, 2017)
This study conducted longitudinal comparisons of US and Dutch paternal ratings of temperament, measured via the Infant Behaviour Questionnaire-Revised, at 4 months (US n= 99; Dutch n= 127) and 12 months (US n= 66; Dutch n= 112) of age. US fathers rated their infant higher in the broad temperament trait Surgency, and its subscales vocal reactivity, high-intensity pleasure, and activity level. US fathers also rated their infants higher in Negative Emotionality, and its subscales of sadness, distress to limitations, and fear. Dutch infants received higher ratings in falling reactivity. Though the cultures did not differ in ratings of Orienting/regulatory capacity, US infants were higher on the subscale duration of orienting, and lower in soothability. Significant culture-by-age and culture-by-gender interactions were also noted. Overall, results are largely consistent with those reported for Dutch mothers (Sung et al., 2014) and speak to considerable differences in early temperament development between cultures viewed as largely similar because of their Western/individualistic orientations.